Investigation of the effect of electric field on bacteria isolated from skin infection - RABAB BASSIM AL-SALAMI; EMAN ABOOB MUKHAIFI; WIJDAN HUSSEIN AL-TAMIMI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Al-Salami RB, Mukhaifi EA, Al-Tamimi WH. 2024. Investigation of the effect of electric field on bacteria isolated from skin infection. Biodiversitas 25: 1320-1328. Nineteen bacterial isolates were obtained from twenty-six samples obtained from various patients with skin infections in the current study. These bacteria were identified by a genetic method depending on 16S rRNA and the molecular identification of cna and fnbA genes of Staphylococcus aureus isolates were detected, and an antimicrobial electric field was applied using various voltages and durations to target both Gram-positive and Gram-negative bacteria. The results showed that Staphylococcus sp. was the most dominant genera, followed its Acinatobacter sp. The high frequent species was Staphylococcus aureus (24%) followed by Staphylococcus epidermidis (21%), Staphylococcus epidermidis and Staphylococcus argenteus (10.5%), Staphylococcus haemolyticus, Acinetobacter baumannii and Acinetobacter variabilis (5.2%). Eleven new strains were identified and recorded in GenBank. A phylogenetic tree was also constructed based on 16S rRNA gene sequences of isolates to evaluate their close relationship and evolution between them. The bands of each amplified cna and fnbA gene were described at 192 bp and 191 bp respectively. The effect of the antimicrobial electric field showed an extremely high and significant decrease of the viable bacterial count of S. haemolyticus and A. baumannii after the exposure to an electric field of (1-5) V for 15 min, where the viable count of bacteria reduced sharply with percentage bacterial death (19-95%) and (16-100%), respectively, and from (66-100%) and (52-100%) after 30 min, respectively.